Assessment of knowledge, awareness, and attitude toward genetic diseases among medical students studying in a tertiary health-care teaching hospital in Uttarakhand, India - Johar, Pulkit; Puri, Oshin; Kumar Verma , Prashant (Indian Journal of Child Health, 2024)
There is a high prevalence of genetic disorders in India. Factors that favor high prevalence are the large population, high birth rate, and consanguineous marriage in many communities. The majority of physicians rely upon knowledge of medical schools gained at the undergraduate level. Currently, at the undergraduate level Medical Genetics, is being taught by different departments in different semesters. It creates a lack of continuity and integrity. This Study identified that medical students have limited knowledge about basic medical genetics, moderate awareness regarding the epidemiological and social impact of genetic diseases and an optimistic attitude towards management of genetic diseases in the society. Curricular teaching and practical exposure might be helpful in increasing the knowledge and awareness and inculcate practicality in students’ attitude.